PROGRAM PENGUATAN LITERASI KEUANGAN SYARIAH BAGI PEMUDA KARANG TARUNA SEBAGAI UPAYA MENINGKATKAN KEMANDIRIAN EKONOMI - Adi Basuki Choirul; Dimas Wahyu Rozaki; Muhammad Adi Adrian; Moh. Kaisul Afkar; Muhammad Fatur Rahman; Anis Ilham (DEVELOPMENT: Journal of Community Engagement, 2026)
This community service activity aims to strengthen Islamic financial literacy among youth members of the Karang Taruna organization in Prasung Village, Sidoarjo Regency, through Islamic financial literacy education. This program was motivated by the limited level of Islamic financial literacy among Karang Taruna youth, which is considered an important factor in enhancing economic independence. The study employed a descriptive-participatory approach through Participatory Action Research (PAR), as it actively involves Karang Taruna members in identifying problems, formulating solutions, and evaluating program activities. Through the PAR approach, participants were not merely the objects of the program but also acted as active subjects directly involved in strengthening Islamic financial literacy and fostering economic self-reliance. The results indicate that the program was effective in improving the Islamic financial literacy capacity of Karang Taruna youth while simultaneously encouraging the development of economic independence among young people in Prasung Village. Furthermore, the program contributed to increasing youth motivation to achieve economic self-reliance through productive activities and more prudent financial management. Therefore, strengthening Islamic financial literacy can serve as an effective community empowerment strategy to support inclusive, productive, and sustainable rural economic development.